Impact of house prices on household carbon emissions - Cong, Ying; Wang, Yanxu; Wu, Yanlin (Frontiers in Environmental Science, 2023)
Carbon emissions generated by household activities are an important factor in climate change; reducing household carbon emissions (HCEs) will be an essential part of future energy conservation and sustainability initiatives. Housing prices have a crucial impact on residents’ consumption, and the increase of consumption level is the main reason for the rise of household carbon emissions. Therefore, studying the impact of housing prices on HCEs not only provides guidance on expanding domestic demand and increasing consumption from the perspective of housing prices but also provides construction advice on curbing global warming and is more conducive to the development of building sustainable consumption. Taking household consumption as a starting point, this study investigates the impact of house prices on HCE in China based on the 2018 Chinese Household Tracking Survey (CFPS) and the China Energy Statistics Yearbook, using the carbon emission factor method to measure carbon emissions. It was found that increased house prices had a significant positive effect on HCEs. There is a clear wealth effect of rising house prices among homeowners, while the substitution effect also increases consumption among non-homeowners (by reducing attempts to save). Furthermore, rising house prices have a varied effect on different types of HCEs. The impact on emissions from everyday necessities such as clothing and housing is greater, and the impact on entertainment-related carbon emissions is small. In addition, rising house prices had the strongest effect on HCEs in central China. Homeowners in the east responded more to increased house prices than in the west, while the inverse effect was observed among non-homeowners. Urban homeowners and rural non-homeowners were also more sensitive to rising house prices. Policy recommendations are made based on the findings.